2021
DOI: 10.1186/s12974-021-02243-7
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine prevents and reverses neuroimmune induction and loss of adult hippocampal neurogenesis following adolescent alcohol exposure

Abstract: Background Binge ethanol exposure during adolescence reduces hippocampal neurogenesis, a reduction which persists throughout adulthood despite abstinence. This loss of neurogenesis, indicated by reduced doublecortin+ immunoreactivity (DCX+IR), is paralleled by an increase in hippocampal proinflammatory signaling cascades. As galantamine, a cholinesterase inhibitor, has anti-inflammatory actions, we tested the hypothesis that galantamine would prevent (study 1) or restore (study 2) AIE induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…Thus, induction of HMGB1→TLR4/ RAGE→pNFκB p65 signaling cascades may be a critical mediator in AIE-induced cell death of neuroprogenitors, as expression of hippocampal pNFκB p65 and cleaved caspase-3 are highly correlated (He and Crews, 2007). Furthermore, reversal of hippocampal proinflammatory cascades through the cholinesterase inhibitor galantamine prevents and reverses both AIE induction of HMGB1, COX-2, and CCL2 as well as reduces AIE induction of cleaved caspase-3 in DCX-labeled immature neurons in male rats (Macht et al, 2021), further highlighting that disruption of cholinergic signaling contributes to AIE induction of neuronal inflammatory proinflammatory cascades, cell death, and adult hippocampal neurogenesis.…”
Section: Adolescent Binge Ethanol Exposure Impairs Adult Hippocampal ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, induction of HMGB1→TLR4/ RAGE→pNFκB p65 signaling cascades may be a critical mediator in AIE-induced cell death of neuroprogenitors, as expression of hippocampal pNFκB p65 and cleaved caspase-3 are highly correlated (He and Crews, 2007). Furthermore, reversal of hippocampal proinflammatory cascades through the cholinesterase inhibitor galantamine prevents and reverses both AIE induction of HMGB1, COX-2, and CCL2 as well as reduces AIE induction of cleaved caspase-3 in DCX-labeled immature neurons in male rats (Macht et al, 2021), further highlighting that disruption of cholinergic signaling contributes to AIE induction of neuronal inflammatory proinflammatory cascades, cell death, and adult hippocampal neurogenesis.…”
Section: Adolescent Binge Ethanol Exposure Impairs Adult Hippocampal ...mentioning
confidence: 99%
“…Ki67 is expressed during mitosis across mammalian species and exhibits a very short half-life, making it a conservative but accurate estimate of actively dividing cells in the subgranular zone of the neurogenic niche. Some ( Nixon and Crews, 2002 ; Taffe et al, 2010 ; Vetreno and Crews, 2015 ; Liu and Crews, 2017 ) but not all ( Ehlers et al, 2013 ; Broadwater et al, 2014 ; Macht et al, 2021 ) studies have found that adolescent binge ethanol exposure decreases Ki67 immunoreactivity in adulthood. Conversely, adolescent binge ethanol exposure has consistently been found to induce activation of the apoptotic executioner caspase cleaved caspase-3 ( Ehlers et al, 2013 ; Broadwater et al, 2014 ; Vetreno and Crews, 2015 ; Liu and Crews, 2017 ; Macht et al, 2021 ), and/or to increase hippocampal necrotic cell death, as marked by Fluoro-Jade B ( Taffe et al, 2010 ; Ehlers et al, 2013 ), across species and across variations in route of administration.…”
Section: Fetal Alcohol Spectrum Disorder (Fasd) and The Lasting Devel...mentioning
confidence: 99%
See 3 more Smart Citations